2003
DOI: 10.1046/j.1525-1446.2003.20403.x
|View full text |Cite
|
Sign up to set email alerts
|

State of Evaluation: Community Health Workers

Abstract: This paper presents the findings of a qualitative research which analyses the characteristics of the evaluation process of community health agents' work. The research was undertaken in three different municipalities. Community health agents, their supervisors, and Primary Health Care managers took part in the investigation, which consisted of semi-structured interviews and focus groups. The discussion was organized according to content analysis, and based on the concept of health work process. Four categories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 16 publications
1
73
0
Order By: Relevance
“…Eight reviews were found that amalgamated lessons learned and suggested key enabling features that can increase likelihood of CHW program success. These were reports by Gilson et al (1989), OfosuAmaah (1983), Witmer et al (1995), Bhattacharyya et al (2001), Nemcek andSabatier (2003), Lehmann, Friedman and Sanders (2004), Haines et al (2007), Gilroy & Winch (2005) and Lehmann and Sanders (2007). In addition, two large reviews evaluated the literature on CHW programs to determine their effectiveness: Lewin et al (2005) and Swinder (2005).…”
Section: Literature Review Overviewmentioning
confidence: 84%
See 1 more Smart Citation
“…Eight reviews were found that amalgamated lessons learned and suggested key enabling features that can increase likelihood of CHW program success. These were reports by Gilson et al (1989), OfosuAmaah (1983), Witmer et al (1995), Bhattacharyya et al (2001), Nemcek andSabatier (2003), Lehmann, Friedman and Sanders (2004), Haines et al (2007), Gilroy & Winch (2005) and Lehmann and Sanders (2007). In addition, two large reviews evaluated the literature on CHW programs to determine their effectiveness: Lewin et al (2005) and Swinder (2005).…”
Section: Literature Review Overviewmentioning
confidence: 84%
“…CHWs must be people who are already trusted members of the community (Nemcek and Sabatier 2003), who plan to stay in the community (Robinson & Larsen 1990) and who reflect the linguistic and cultural diversity of the population served (Witmer et al1995). Selecting workers who are not trusted and respected by the community, who misunderstand their role or have unrealistic expectations leads to high attrition rates, poor worker performance, and low community engagement with the program (Bhattacharyya et al 2001;Nemcek and Sabatier 2003;Witmer et al 1995).…”
Section: Appropriate Selectionmentioning
confidence: 99%
“…These results suggest that community health workers may be most successful at using MI techniques to encourage behavioral change with families, likely due to their unique understanding of cultural and community-specific concerns (Nemcek & Sabatier, 2003 (Miller & Rollnick, 2002).…”
Section: Practitioner Professionmentioning
confidence: 99%
“…Models of engagement that emphasize empowerment of local leaders who remain embedded in diverse social networks have been associated with feminist theory [21], community-based conservation theory [22], and the public health field [23,24].…”
Section: Literature Reviewmentioning
confidence: 99%